ANALISIS DAMPAK DARI PEMBANGUNAN PERUMAHAN CITRA PESONA INDAH TERHADAP POTENSI KONDISI EKONOMI MASYARAKAT - Zulhipni, Zulhipni (Katalogis, 2015)
The aim of this study is to determine the impact of the construction of the CPI Housing toward the potentitial growing of new trade ventures and the potential increase of value of land sales in the year of 2016-2020 located in the residential area of ​​the CPI. The research sample is designated as 30 respondents, consisting of 10 residential occupants, 10 merchants and 10 landowners. Data were collected by questionnaire distribution techniques, observation, interviews and documentation. And then, the data were analyzed descriptively, using qualitative and quantitative approaches, where this research was described in detail and clearly. To answer the first question, it is used statistical tests non parametric ie Two Related Samples Tests (with the Wilcoxon test) and qualitative analysis that is Crosstabs and to answer the second problem it is used statistical parametric tests ie Paired Samples T Test and for method of population growth it is used Geometry models that has been modified according to the needs of this research. Results of this study concluded that: 1) the construction of CPI housing resulted in the increase of traders’ income and it impctas on the growth potential of new businesses in the residential area. 2) CPI Housing construction also gives positive impact on the increase in land selling value and the potential increase of land selling is three (3) areas which are located in and around the CPI residential area, they are the Dayodara area inside the residential complex, Dayodara area outside the residential complex, and Poboya area.